Short Communication Isolation of Aromatic Sulphone from Plumbago zeylanica Linn. (Biological Sciences - PJSIR, 2007)
Diphenyl sul phone and -sitosterol were isolated from the petroleum ether extract of stem of Plumbago zeylanica Li nn . They were character i zed by spectroscop i c method s. I solation of diphenyl sulphon e from th i s plant is the first report from h i gher pl ants. Diphen y l sulphone was tested for cytotoxici ty by bri ne shrimp lethality test.